Pharmacognosy, Phytochemical, and Pharmacology of Wijaya Kusuma (Epiphyllum oxypetalum (DC.) Haw.) – An Update Review - Chandra Adam Lesmana; Ni Putu Ermi Hikmawanti; Agustin Yumita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
In Indonesia, Epiphyllum oxypetalum (DC.) Haw. is known as Wijaya Kusuma. The plant is grown for home decorating and used widely as medicine in some areas. This narrative review discusses the pharmacognosy, phytochemical, and pharmacology aspects of E. oxypetalum. The review is limited to original articles and abstracts available in Science Direct, PubMed, and Google Scholar. The keyword used to search the articles was “Epiphyllum oxypetalum”. The plant contains proteins, amino acids, alkaloids, saponins, terpenoids, steroids, flavonoids, tannins, glycosides, and resins. The plant has pharmacological activities such as anti-inflammatory, antimicrobials, antidiabetic, and antioxidant properties. Researchers interested in developing E. oxypetalum as a medicinal plant might use this review as a reference.